Meat freezing : a source book - Berry, Brad W. (Brad William), 1941- (Developments in food science, 1989)
This book provides a comprehensive summary of the published research related to freezing of meat and poultry products. Among the aspects dealt with are: freezing rate, frozen storage temperature, frozen storage time, temperature fluctuations, thawing and packaging, and their influence on microbiology, storage life indicators, palatability, texture, histology, cooking properties, weight losses and chemical constitutents of red meat and poultry products. The information is presented in an easy-to-use tabular form. Summaries of individual research reports and papers are divided into fourteen main sections. For each summary, the Factors Studied and Characteristics Evaluated are first identified. A concise, yet sufficiently detailed, description of the Purpose and Methodology is given, followed by Results and Comments. A general conclusion, interpretation or comment determined by the original authors, the authors of this book, or both is presented under the heading of General Comments, and each summary concludes with the complete reference citation. Meat Freezing will serve as a useful source of information for those involved in research or conducting literature reviews in this area.